Dynamically tuning the optical properties of Europium-doped sodium niobate nano-crystals through magnetic field. (11th November 2016) - Xiao, Quanlan; Zhang, Yuanhao; Zhang, Junpei; Zhang, Han; Dong, Guoping; Han, Junbo; Qiu, Jianrong
Abstract: We have fabricated high quality NaNbO3 :Eu 3+ nano-crystals based on the Pechini sol-gel method and realized its magneto-optical effect under external pulsed magnetic field. Our results show that magnetic field can induce the suppression of luminescence, the splitting of peaks, and shifting of peak locations due to the expansion of electric dipole emission in Europium ions, and further demonstrate that the magnetic dipole emission plays an insignificant role in effect on the magnetic dipole emission for Eu 3+ : 5 D 0  →  7 F 1, 5 D 0  →  7 F 3 transitions in NaNbO3 :Eu 3+ nano-crystals. These magnetic-optical interactions are attributed to the results of the Zeeman effect by high magnetic field that could result in the change of the symmetry of Eu 3+ ions, and there is different sensitivity to changes of symmetry for Eu 3+ : 5 D 0  →  7 F J ( J  = 1–4) transitions in NaNbO3 nano-crystals. This work might provide a viable magneto-optical approach in tuning the optical properties (luminescence intensity, peak location, profile, etc) of the rare-earth ions doped nano-particles.